Desire and Debt Satisfaction in Anselm of Canterbury and Hadewijch of Brabant - Landrith, Robin (Modern theology, 2025)
“Satisfaction” is the famous epithet given to Anselm's atonement theory. Less well appreciated even in modern retrievals of Hadewijch's work is the centrality of “satisfaction” as a concept for her, being just as technical but more theologically extensive in her writing than it is in Anselm's. Despite cultural similarities, the meaning of satisfaction in their respective works differs. This article argues that the difference between the concepts of satisfaction in Anselm's Cur Deus Homo and Hadewijch's Brieven depends on the difference between the meaning of the “debt” that the satisfying act satisfies. Anselm's “satisfaction” (satisfactio) responds to the debt created by sin, while Hadewijch's “satisfaction” (ghenoeghen) responds to the debt created by love's demand—a debt not only, or even primarily, of the beloved to the lover, but of the lover to the beloved. Departing from depictions of debt in both medieval and modern theology, Hadewijch presents indebtedness per se not as a point of contrast between human beings and God. Instead, she suggests that atonement recreates human understanding to perceive the original meaning of debt, which is the debt of love that the divine persons “eternally demand and eternally render” from and for each other.